Body mass index and muscle strength in medical students - Apen A Ridwan; Hedi H Rachmatdinata; Ilham F Saputra (ACTA Medical Health Sciences, 2025)
Body mass index (BMI) is an indicator of nutritional status that affects health and muscle strength. Obesity inhibits adenosine monophosphate activated protein kinase (AMPK), thereby reducing endurance, decreasing muscle function, and increasing disease risk. This study aims to determine the relationship between BMI and muscle strength. A cross-sectional analyticalstudy was conducted among preclinical students of the Faculty of Medicine, Universitas Jenderal Achmad Yani. BMI, grip strength, and standing long jump performance were measured in all respondents. Data were analyzed using Statistical Product and Service Solutions (SPSS). The results showed that most students had a normal BMI (50%), indicating good nutritional status. All respondents with overweight and obesity class I and II BMI demonstrated standing long jump results far below the average (100%), while only 7.1% of respondents with normal BMI reached the average category. Most respondents with normal BMI had normal hand strength (57.1%), as did those with obesity class II (83.3%). Statistical analysis using the chi-square test showed no significant relationship between BMI and muscle strength, with pvalues of 0.629 and 0.792. In conclusion, most students had a normal BMI, normal handgrip strength, and low standing long jump performance. There was no significant relationship between BMI and muscle strength.   DOI : 10.35990/amhs.v4n2.p87-93   REFERENCES Nuttall FQ. Body mass index: Obesity, BMI, and health: A critical review. Nutrition Today. 2015;50:117–128. Khanna D, Peltzer C, Kahar P, Parmar MS. Body mass index (BMI): A screening tool analysis. Cureus. 2022;14. Catatan: nomor artikel/e-location & nomor edisi belum dicantumkan (hanya “Feb 11”). Adab P, Pallan M, Whincup PH. Is BMI the best measure of obesity? BMJ. 2018;k1274. Gutin I. In BMI we trust: Reframing the body mass index as a measure of health. Social Theory & Health. 2018;16(3):256–271. Sihombing MRBS, Siregar NP, Ismail WM, Bestari R. Relationship between body mass index and upper and lower limb muscle strength in athletes of Zauzy Taekwondo Club, Binjai. Ibnu Sina: Jurnal Kedokteran dan Kesehatan (Fakultas Kedokteran Universitas Islam Sumatera Utara). 2024;23(2):138–144. Zierle-Ghosh A, Jan A. Physiology, body mass index. StatPearls [Internet]. 2023. Tersedia pada: https://www.ncbi.nlm.nih.gov/books/NBK535456/ Keevil VL, Luben R, Dalzell N, Hayat S, Sayer AA, Wareham NJ, et al. Cross-sectional associations between different measures of obesity and muscle strength in men and women in a British cohort study. Journal of Nutrition, Health & Aging. 2015;19(1):3–11. Bennie JA, Shakespear-Druery J, De Cocker K. Muscle-strengthening exercise epidemiology: A new frontier in chronic disease prevention. Sports Medicine - Open. 2020;6(1):40. Cianferotti L, Brandi ML. Muscle–bone interactions: Basic and clinical aspects. Endocrine. 2014;45(2):165–177. Srinivas-Shankar U, Roberts SA, Connolly MJ, O’Connell MDL, Adams JE, Oldham JA, et al. Effects of testosterone on muscle strength, physical function, body composition, and quality of life in intermediate-frail and frail elderly men: A randomized, double-blind, placebo-controlled study. Journal of Clinical Endocrinology & Metabolism. 2010;95(2):639–650. Intan K, Dewi M, Ayu I, Widiastuti E, Ayu AA, Wedayani N. Relationship between body mass index and muscle strength in medical students at Universitas Mataram. Jurnal Kedokteran Unram. 2020;9(1):63–72. Soraya N, Parwanto E. The controversial relationship between body mass index and handgrip strength in the elderly: An overview. Malaysian Journal of Medical Sciences. 2023;30(3):73. Lin X, Li H. Obesity: Epidemiology, pathophysiology, and therapeutics. Frontiers in Endocrinology (Lausanne). 2021;12. Tersedia pada: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC8450866/ Núñez-Cortés R, Cruz B del P, Gallardo-Gómez D, Calatayud J, Cruz-Montecinos C, López-Gil JF, et al. Handgrip strength measurement protocols for all-cause and cause-specific mortality outcomes in more than 3 million participants: A systematic review and meta-regression analysis. Clinical Nutrition. 2022;41(11):2473–2489. Castro-Piñero J, Ortega FB, Artero EG, Girela-Rejón MJ, Mora J, Sjöström M, et al. Assessing muscular strength in youth: Usefulness of standing long jump as a general index of muscular fitness. Journal of Strength and Conditioning Research. 2010;24(7):1810–1817. Ceschia A, Giacomini S, Santarossa S, Rugo M, Salvadego D, Da Ponte A, et al. Deleterious effects of obesity on physical fitness in pre-pubertal children. European Journal of Sport Science. 2016;16(2):271–278. Krishnan A, Sharma D, Bhatt M, Dixit A, Pradeep P. Comparison between standing broad jump test and Wingate test for assessing lower limb anaerobic power in elite sportsmen. Medical Journal Armed Forces India. 2017;73(2):140–145. Rahman ZA. Reliability, validity, and norm references of standing broad jump. Revista Gestão Inovação e Tecnologias. 2021;11(3):1340–1354. Tomlinson DJ, Erskine RM, Morse CI, Winwood K, Onambélé-Pearson G. The impact of obesity on skeletal muscle strength and structure through adolescence to old age. Biogerontology. 2016;17:467–483. Pasdar Y, Darbandi M, Mirtaher E, Rezaeian S, Najafi F, Hamzeh B. Associations between muscle strength with different measures of obesity and lipid profiles in men and women: Results from RaNCD cohort study. Clinical Nutrition Research [Internet]. 2019;8(2):148. Martínez EJ, Martínez-López M, López L, Torre-Cruz LA, Suárez S, et al. Analysis of the effect size of overweight in muscular strength tests among adolescents: Reference values according to sex, age, and body mass index. Journal of Strength and Conditioning Research. 2018;32(5):1404–1414. Thivel D, Ring-Dimitriou S, Weghuber D, Frelut ML, O’Malley G. Muscle strength and fitness in pediatric obesity: A systematic review from the European Childhood Obesity Group. Obesity Facts. 2016;9(1):52–63. Hall JE. Guyton and Hall Textbook of Medical Physiology. 13th ed. 2018. p. 80. Tallis J, James RS, Seebacher F. The effects of obesity on skeletal muscle contractile function. Journal of Experimental Biology. 2018;221(13). Al-Asadi JN. Handgrip strength in medical students: Correlation with body mass index and hand dimensions. Asian Journal of Medical Sciences [Internet]. 2018;9(1):21–26.